2020
DOI: 10.1038/s41438-020-0291-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the diversity of tomato: the development of a phenotypically and genetically detailed germplasm collection

Abstract: A collection of 163 accessions, including Solanum pimpinellifolium, Solanum lycopersicum var. cerasiforme and Solanum lycopersicum var. lycopersicum, was selected to represent the genetic and morphological variability of tomato at its centers of origin and domestication: Andean regions of Peru and Ecuador and Mesoamerica. The collection is enriched with S. lycopersicum var. cerasiforme from the Amazonian region that has not been analyzed previously nor used extensively. The collection has been morphologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 53 publications
2
65
1
1
Order By: Relevance
“…cerasiforme , further evolution of which in Mesoamerica resulted in S. lycopersicum var. lycopersicum [ 38 , 39 ] that, together with its 12 wild relatives, now form Solanum section Lycopersicon [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cerasiforme , further evolution of which in Mesoamerica resulted in S. lycopersicum var. lycopersicum [ 38 , 39 ] that, together with its 12 wild relatives, now form Solanum section Lycopersicon [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tomato diversification due to domestication is distinct from the natural species divergence as it passed through various genetic bottlenecks caused by the selection of a limited set of traits valuable for humans, which significantly limited genomic diversity among modern S. lycopersicum cultivars [ 36 , 40 , 41 ]. As a result, S. lycopersicum differs from its wild ancestors in a wide range of acquired morphophysiological characteristics (so-called domestication syndrome) and in genetic diversity, which constitutes no more than 5% of that existing among wild tomatoes [ 39 ]. Fruit color and carotenoid content are included in the domestication syndrome; these features are controlled by qualitative trait genes, including PSY1 encoding phytoene synthase, the key enzyme of carotenogenesis in fruit, which has a conserved structure but also contains polymorphisms associated with the evolution of plant species [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, SLC3 and SLC4 are the most similar to the cultivated tomato in terms of morphological traits, and consequently, they group far from the other accessions in the PCA. In fact, the existence of high variability in morphological traits in SLC was already highlighted by Rick and Holle 57 and corroborated later by Blanca et al 4 and Mata-Nicolás et al 58 , who demonstrated the presence of fas (fasciated), loc (LOC), and fw2.2 and fw3.2 (FW) and ovate alleles in SLC coming from Ecuador and Peru, which was determinant to the increase of FW and diversification of FS. In some cases, SLC has been even sold in local markets 59 and, for this purpose, some unconscious selections may have been performed by growers, mainly increasing its fruit size.…”
Section: Discussionmentioning
confidence: 58%
“…The focus of modern breeding programs for fresh market use of tomato have usually laid emphasis on resistance, yield, and quality attributes such as firmness, color, texture, and traits related to fruit appearance (Foolad, 2007) rather than on sustainable production and nutritional quality (Mata-Nicolás et al, 2020).…”
Section: Introductionmentioning
confidence: 99%